Poliandri dalam Perspektif Pancasila dan Hukum Islam: Kajian Konstitusional dan Nilai-Nilai Kebangsaan: Polyandry in the Perspective of Pancasila and Islamic Law: Constitutional Studies and National Values - Ahmad Muhammad Mustain Nasoha; Ashfiya Nur Atqiya; Marsha Cahya Shakilla; Nur Amalina; Aini Zulaika; Isna Maziyah Agustin (DIRASAH: Jurnal Kajian Islam, 2024)
The phenomenon of polyandry in Indonesia has given rise to debate regarding individual rights and freedom in choosing a partner, which has begun to be advocated by some community groups in the context of human rights. However, this practice is not recognized in Indonesian positive law and is considered inconsistent with the values ​​of Pancasila, especially the principles of "Belief in One Almighty God" and "Just and Civilized Humanity." This research aims to analyze the compatibility of polyandry practices with the principles of Pancasila and Indonesian positive law and consider the Islamic perspective as a strong moral foundation in society. Using a juridical-normative approach, this research examines the relationship between social development and family law regulations in Indonesia. The results of the research show that although polyandry is considered an individual right, this practice is contrary to Islamic teachings and Pancasila values, indicating the need to strengthen the role of education and review the Marriage Law so that it is more responsive to social dynamics, but still adheres to existing values. underlies the Indonesian nation.